The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.iecr.5b00574
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Catalytic Activities of Hydrothermally Synthesized Bilayered HZSM-5 Coatings with Additional Nonzeolite Pores

Abstract: Bilayered HZSM-5 zeolite coatings with additional nonzeolite pores were synthesized on the inner surface of stainless steel tubes by a secondary growth method with the addition of ethanol into the synthesis batch. The as-synthesized coatings were characterized by scanning electron microscopy and gas permeation, indicating that additional nonzeolitic pores were formed in the presence of ethanol. A remarkable greater than 1000-fold improvement in N2 permeation was observed. Catalytic cracking of supercritical n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…One effective approach to improve reactants diffusion inner films is to introduce additional nonzeolite (or intercrystal) pores by adding ethanol into the synthetic solutions, which gives an activity improvement by ca. 150% in catalytic cracking of n ‐dodecane . Another innovation idea is to prepare highly b ‐oriented ZSM‐5 films and thus to selectively use the straight and larger pores (0.53 × 0.56 nm 2 ) along b axis.…”
Section: Methodsmentioning
confidence: 99%
“…One effective approach to improve reactants diffusion inner films is to introduce additional nonzeolite (or intercrystal) pores by adding ethanol into the synthetic solutions, which gives an activity improvement by ca. 150% in catalytic cracking of n ‐dodecane . Another innovation idea is to prepare highly b ‐oriented ZSM‐5 films and thus to selectively use the straight and larger pores (0.53 × 0.56 nm 2 ) along b axis.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 displays the XRD patterns of the HZSM-5 membranes. For all samples, there were several typical diffraction peaks corresponding to the characteristic peaks of the MFI topology, indicating a successful crystallization of the HZSM-5 phase on the stainless steel tubes (SST) [18]. With the TPOAC/TEOS ratios in the synthesis gel growing from 0 to 0.15, the relative crystallinities of the HZSM-5 membranes decreased gradually (as shown in Table 1), which was in line with the observation of Peng et al [24] and Cho et al [31].…”
Section: Structures Characterizationmentioning
confidence: 99%
“…N 2 permeance through the zeolite membranes was selected to reflect the diffusivity of the membrane; it has been reported that the high permeance value implies a high diffusivity [18,33]. As seen in Table 1, the values of the N 2 permeance increased, monotonously, with both the TPOAC/TEOS and TMB/TPOAC ratios.…”
Section: Gas Permeation Propertiesmentioning
confidence: 99%
See 2 more Smart Citations